Analisis SWOT Pemahaman Mahasiswa Mata Kuliah Kantor Depan di Kelas IIA D3 Prodi Perhotelan AKPAR Denpasar - Ida Bagus Nyoman Bala Putra (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
This study aims to analyze students' understanding of the Front Office course using a SWOT approach in the D3H IIA class of the Hospitality Study Program at the Denpasar Tourism Academy. A descriptive qualitative method was employed through triangulation techniques, including observation, questionnaires, and interviews, to obtain comprehensive data on the strengths, weaknesses, opportunities, and threats in the learning process. The findings show a high level of student enthusiasm, with a 99% attendance rate. Students with a hospitality educational background performed better in mastering the material and participating actively. Conversely, non-hospitality students demonstrated limited technical understanding and discipline. Opportunities are available for all students to pursue front office positions, provided they are equipped with adequate knowledge, skills, and professional attitudes. However, intense competition and increasing demands for soft skills pose real threats to students entering the job market. This study recommends enhancing integrated theory-practice learning and developing student character and social competencies to strengthen competitiveness in the hospitality industry.